Nilai-Nilai Pendidikan Islam Multikultural dalam Kegiatan Al-Islam dan Kemuhammadiyahan - Syakban, Ismail; Aryani, Sekar Ayu; Saputra, Riki (Al-Liqo: Jurnal Pendidikan Islam, 2024)
Differences in understanding of beliefs, cultures, regions, and Islamic organizations at Muhammadiyah University of West Sumatra have triggered conflicts on behalf of groups, causing exclusivity and fragmentation in the campus environment. The lack of openness and communication between different groups further exacerbates the situation. Therefore, the integration of multicultural Islamic education values in learning and activities of Al-Islam and Kemuhammadiyahan (AIK) is needed. This study aims to analyze and reveal the inclusive, egalitarian, and humanist values applied in the activities. Using a qualitative case study approach, observation, interviews, and documentation to collect data. Data analysis through data reduction procedures, data display, and conclusion drawing. The results showed that multicultural-based AIK activities were able to reduce conflict by internalizing inclusive values in every activity, thus creating a more harmonious and tolerant campus environment. The integration of multicultural values in the curriculum and extracurricular activities succeeded in increasing understanding and cooperation between different groups.